Crimea : la primera gran guerra - Figes, Orlando (Ensayo histórico (Barcelona, Spain), 2012)
From "the great storyteller of modern Russian historians" comes the definitive account of the Crimean War, a forgotten war that shaped the modern age. Figes reconstructs the first full conflagration of modernity, a global industrialized struggle fought with unusual ferocity and incompetence.